2015
DOI: 10.1007/s12013-014-0433-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PI3K/Akt Signaling Pathway on the Process of Prostate Cancer Metastasis to Bone

Abstract: We sought to study the effects of PI3K/Akt pathway and its downstream substrate NF-κB on prostate cancer bone metastatic process. Expression level of active p-Akt in PC3 cells was upregulated by transient expression with constitutively active plasmid CA-Akt or, alternatively, suppressed by dominant negative construct DN-Akt. NF-κB activity was determined by luciferase reporter assays. mRNA and protein expressions of receptor activator of NF-κB ligand (RANKL), parathyroid hormone-related protein (PTHrP), and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…This inhibition of AKT could then promote FOXO3a and Par-4 activation leading to apoptosis as was demonstrated in prostate cancer cells by Das et al [49]. Also in a report by Zhu et al [50], silencing of prostatic PC3 cells for AKT resulted in reductions of growth promoting RANKL , PTHrP , and BMP-2 . Taken together, our results suggest that CYP1A1 may act as an upstream activator of the PI3K-AKT signaling pathway and enhance the transcriptional activation of anti-apoptotic genes that include BCL2 ; and further studies are needed to verify this hypothesis.…”
Section: Discussionmentioning
confidence: 78%
“…This inhibition of AKT could then promote FOXO3a and Par-4 activation leading to apoptosis as was demonstrated in prostate cancer cells by Das et al [49]. Also in a report by Zhu et al [50], silencing of prostatic PC3 cells for AKT resulted in reductions of growth promoting RANKL , PTHrP , and BMP-2 . Taken together, our results suggest that CYP1A1 may act as an upstream activator of the PI3K-AKT signaling pathway and enhance the transcriptional activation of anti-apoptotic genes that include BCL2 ; and further studies are needed to verify this hypothesis.…”
Section: Discussionmentioning
confidence: 78%
“…[23][24][25] The PI3K/Akt/mTOR pathway is frequently activated in advanced prostate cancer. [23][24][25] The PI3K/Akt/mTOR pathway is frequently activated in advanced prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we observed that it's downstream signaling pathway, the PI3K/Akt signaling pathway was much more active in PC-3 cells. Zhu et al reported that stimulation of PI3K/Akt/NF-kappaB signaling in PC-3 cells upregulates the expression of the steoclastogenesis factors RANK and PTHrP and the osteoblastogenesis factor BMP-2, which may play roles in a variety of bone metastasis-related processes [ 46 48 ]. These findings indicate a possible role of ST6Gal-I in PC-3 cell bone metastasis.…”
Section: Discussionmentioning
confidence: 99%